A CROSS SECTIONAL STUDY OF PREVALENCE AND AWARENESS OF ‘NEEDLE-STICK INJURIES’ IN MEDICAL AND PARAMEDICAL PROFESSIONALS - Zanzrukiya, Kalpesh; Rajdev, Bhaumesh; Pandya, Dhaval; Bhalodiya, Ashish (Journal of Forensic Medicine and Toxicology, 2025)
Background: Needle Stick Injuries(NSI) are accidental skin penetrating injuries by sharp medical instruments to healthcare professionals which may transmit infections or diseases. This occupational injury needs to be addressed seriously. We conducted a cross sectional study regarding prevalence and awareness of NSI among medical and paramedical professionals. Objectives : To assess the awareness of medical and paramedical professionals regarding Needle Stick Injuries and related aspects. To discover the prevalence of needle stick injuries in medical and paramedical professionals. Materials & Methods: We conducted a cross sectional observational study with pre-validated questionnaire. Total 100 participants were enrolled as per inclusion and exclusion criteria. Collected data analyzed & reported. Results: 43% participants were doctors, 33% were nurses, 12% were dentists and 12% were paramedical professionals. 45% participants were from paramedical branch, 39% from surgical branch, 13% were from general and 3% were from medicine & allied branches. 83% participants answered that they were aware about PreExposure Prophylaxis Guidelines for HIV, while 17% were not aware. 85% participants answered that they get regular training for proper use and disposal of sharp instruments, 15% answered No for it. 26% subjects were right about how long a needle remains infective for HIV, HBV & HCV after use, 26% were partially correct and majority subjects 48% were wrong. 53% participants answered correct about what investigations to be done in oneself if get injured by NSI, 12% gave wrong answer while 53% were partially correct. 23% participants had got injured by NSI during their professional works. 43% were aware about immediate steps after getting NSI. 59% got HBV Vaccine every 5yrly, while 24% got it only once and 17% didn’t remember or not taken. Conclusion: The prevalence of NSI in our study was 23%. Majority participants were aware about NSI, but the knowledge and practice of majority of them were either wrong or partially correct. NSI is a common work place injury among medical and paramedical professions so, awareness & alertness about it are necessary.
Keywords: Needle Stick Injury; Sharp injury; Work place injury; Occupational injury